Hydrogen Demand Data of an average size farm in the UK - Huo, Da; Balta-Ozkan, Nazmiye (Cranfield University, 2025)
Green hydrogen offers a transformative yet underexplored pathway for agricultural de-carbonisation, requiring technological readiness and coordinated action from policymakers, industry, and farmers. To examine its potential, techno-economic analyses were con-ducted for farms ranging from an average size of 123 hectares to clusters of 10 farms. These were complemented by stakeholder engagement, including seven semi-structured interviews and a workshop with nine sector experts. The findings highlight both technical opportunities and significant barriers. While on-farm hydrogen production is technically feasible, it remains economically uncompetitive due to high levelised costs, shaped by seasonal demand variability and low utilisation of electrolysers and storage. Addressing these challenges requires pooling demand across multiple users to improve cost-effectiveness. Stakeholders identified three business models for hydrogen adoption in agriculture: fertiliser production through ammonia synthesis, cooperative-based models, and local refuelling stations. With supportive policy and coordinated action, co-operative hydrogen hubs can cut costs, address farmers’ concerns over affordability, complexity, and adaptability, and transform hydrogen into a practical driver of decarbonisation and rural resilience.
Keywords: Green hydrogen systems; agricultural system decarbonisation